(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The objectives of the study are to estimate the concentrations of trace elements and examine the structural morphology of Taraxcum officinale leaves used in the treatment of certain cancer disorders. Using Scanning Electron Microscope-Energy Dispersive X-ray (SEM-EDX) to analyze the trace elements present in the Taraxcum officinale leaves.